2003
DOI: 10.1002/app.12865
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of volatile depletion for LaRC™‐PETI‐5 amide acid/N‐methylpyrrolidinone solution

Abstract: ABSTRACT:The fabrication of composites from polyimide precursors (polyamide acids) that involve condensation reactions requires the removal of volatiles (solvent and reaction by-products) prior to consolidation in order to achieve a void-free laminate. Volatile removal is commonly accomplished with a B-stage processing step. In this study, a PETAA/NMP (phenylethynyl terminated amide acid in Nmethylpyrrolidinone) solution and prepreg were characterized using therogravimetric analysis (TGA) and microdielectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The polyimide oligomers could be thermally cured into the thermosetted polyimide resins, and the thermal cure temperature of 3718C that we chose was the general thermal cure temperature of phenylethynyl endcapped polyimides for the primary evaluation on properties [18,24]. Figure 6 shows DMA curves of representative thermosetted polyimide resins (PI-1 and PI-2) and Table 4 summarizes the thermal properties of the thermally cured polyimide resins determined by DSC, DMA, and TGA.…”
Section: Thermal Properties Of the Thermally Cured Polyimide Resinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyimide oligomers could be thermally cured into the thermosetted polyimide resins, and the thermal cure temperature of 3718C that we chose was the general thermal cure temperature of phenylethynyl endcapped polyimides for the primary evaluation on properties [18,24]. Figure 6 shows DMA curves of representative thermosetted polyimide resins (PI-1 and PI-2) and Table 4 summarizes the thermal properties of the thermally cured polyimide resins determined by DSC, DMA, and TGA.…”
Section: Thermal Properties Of the Thermally Cured Polyimide Resinsmentioning
confidence: 99%
“…The reactive endcapping agents which are commonly used in the polyimide matrix resins include maleic anhydride (MA) [7,8], nadic anhydride (NA) [9,10], and phenylethynylphthalic anhydride (PEPA) [11][12][13][14][15][16][17][18][19], in which MA and NA have been successfully employed in BMI and PMR (In Situ Polymerization of Monomer Reactants) type polyimide matrix resins [3,20,21]. In recent years, it was found that PEPA has some superior features over NA and MA, such as the stronger polymer chain-extending capability than the chain-crosslinking etc [4,[22][23][24][25][26][27][28][29][30][31]. The PEPA-endcapped polyimide resins showed outstanding thermo-oxidative stability, good mechanical properties, and high toughness.…”
Section: Introductionmentioning
confidence: 99%